2009
DOI: 10.1007/s10867-009-9151-2
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+  modulation of EMCV IRES key activity fragment equilibria and r(G·C) base-pair kinetics

Abstract: NMR magnetization transfer from water and ammonia-catalyzed exchange of the imino proton have been used to probe enhanced thermostability and conformational rearrangements induced by Mg 2+ in two key activity fragments r(CACCUGGCGACAG GUG) and r(GGCCAAAAGCC) of the encephalomyocarditis virus (EMCV) picornavirus internal ribosome entry site (IRES). We have measured some of their r(G · C) base-pair lifetimes and dissociation constants under different MgCl 2 conditions, and we compare them with those of other sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In contrast, we have also shown that the EMCV IRES key activity RNA fragment r(GGCCAAAAGCC) containing the AAAA submotif adopts only a hairpin topology [1]. The present paper is an extension of our earlier article [1]. It completes the experimental study of Mg 2+ effects on the two RNA fragments r(CACCUGGCGACAGGUG) and r(GGCCAAAAGCC) (see Fig.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…In contrast, we have also shown that the EMCV IRES key activity RNA fragment r(GGCCAAAAGCC) containing the AAAA submotif adopts only a hairpin topology [1]. The present paper is an extension of our earlier article [1]. It completes the experimental study of Mg 2+ effects on the two RNA fragments r(CACCUGGCGACAGGUG) and r(GGCCAAAAGCC) (see Fig.…”
Section: Introductionsupporting
confidence: 61%
“…In contrast, we have also shown that the EMCV IRES key activity RNA fragment r(GGCCAAAAGCC) containing the AAAA submotif adopts only a hairpin topology [1]. The present paper is an extension of our earlier article [1].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations